Surface Roughness Scattering of Electrons in Bulk MOSFETS - Zuverink, Amanda (My University, 2015)
Surface-roughness scattering of electrons at the Si-SiO2 interface is a very important consideration when analyzing Si metal-oxide semiconductor eld-e ect transistors(MOSFETs). Scattering reduces the mobility of the electrons and degrades the device performance. 250-nm and 50-nm bulk MOSFETs were simulated with varying device parameters and mesh sizes in order to compare the e ects of surface roughness scattering in multiple devices. The simulation framework includes the ensemble Monte Carlo method used to solve the Boltzmann transport equation coupled with a successive over-relaxation method used to solve the two-dimensional Poisson's equation. Four methods for simulating the surface-roughness scattering of electrons were implemented on both devices and compared: the constant specularity parameter, the momentum-dependent specularity parameter, and the real-space-roughness method with both uniform and varying electric fields. The specularity parameter is the probability of an electron scattering specularly from a rough surface. It can be chosen as a constant, characterizing partially di ffuse scattering of all electrons from the surface the same way, or it can be momentum dependent, where the size of rms roughness and the normal component of the electron wave number determine the probability of electron-momentum randomization. The real-space rough surface method uses the rms roughness height and correlation length of an actual MOSFET to simulate a rough interface. Due to their charge, electrons scatter from the electric field and not directly from the surface. If the electric field is kept uniform, the electrons do not perceive the roughness and scatter as if from a flat surface. However, if the field is allowed to vary, the electrons scatter from the varying electric field as they would in a MOSFET. These methods were implemented for both the 50-nm and 250-nm MOSFETs, and using the rms roughness heights and correlation lengths for real devices. The current-voltage and mobility-electric fi eld curves were plotted for each method on the two devices and compared. The conclusion is that the specularity-parameter methods are valuable as simple models for relatively smooth interfaces. However, they have limitations, as they cannot accurately describe the drastic reduction in the current and the electron mobility that occur in MOSFETs with very rough Si-SiO2 interfaces.